Perlindungan Konsumen dan Tanggung Jawab Perusahaan Ekspedisi terhadap Kasus Kerugian Barang dalam Pengiriman - Salmon, Harly Clifford Jonas (KANJOLI Business Law Review, 2024)
This study discusses the responsibility of expedition companies towards lost consumer goods using a normative juridical research method. The results of the study indicate that regulations related to the shipment of goods by business actors are governed by several laws and ministerial decisions. However, there is often a gap between expedition practices and legal provisions, which leads consumers to feel dissatisfied or disadvantaged. Adequate consumer protection becomes crucial, and there is a need for revisions to the Consumer Protection Law to accommodate the interests of all parties involved. Dispute resolution between consumers and business actors can be carried out through non-litigation channels, such as the Consumer Dispute Settlement Body (BPSK), or through litigation channels. In cases of lost goods caused by expedition companies, these companies are fully responsible in accordance with the principle of liability for negligence. Therefore, expedition companies are obliged to compensate consumers for both material and non-material losses incurred.